School Uniform Entrepreneurship in the Digital Age - Muhammad, Arifin; Rahmah, Annisa Zaini; Lubiis, Nur Asiah; Keling, Mansur (Universitas Ibn Khaldun, 2024)
In entrepreneurship, there are various creativity and innovation, one of the things before running a hero needs to learn management activities, such as planning, organizing, implementing, and evaluating. One of the entrepreneurship in question is school uniforms, during the COVID-19 era there was a decline in the economy, especially school uniforms. But with this, entrepreneurship is developing into the digital world. This research takes the issue related to school uniform entrepreneurs during COVID-19, whether to open sales using digital media or not. This research uses descriptive qualitative research methodology, with case study and interview methods. In marketing in the digital era, there are several things used in social media, namely; collaborative projects, content, and sausage networking sites. In addition, terms of the entrepreneurial industry, especially uniforms can use social media to improve several things such as digital marketing and marketing. By. As a result of the study, out of ten speakers about school uniforms, 3 out of 10 school uniform entrepreneurs wear advice in the digital age and the rest do not, with the opinion that they have collaborated with certain schools to create school uniforms.